Meta-analysis Effect of Compliance with Folic Acid Supplement Consumption in Pregnant Women on the Risk of Birth Defects - Fathia Mutiara Zahra; Frannesty Estu Winahyu; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Low concentrations of folic acid supplement intake during pregnancy can cause birth defects in the baby. Therefore, this study was conducted to identify those associated with adherence to folic acid supplement consumption in pregnant women and provide a shadow for further research. The purpose of this study was to investigate the effect of birth defects and pregnant women's adherence to taking folic acid supplements during pregnancy.Subjects and Method: This study uses the PRISMA flowchart to perform the meta-analysis. The article review process took place between 2017 and 2022 with PICO as follows, Population: Pregnant Women. Intervention: Folic acid consumption before and during pregnancy, Comparison: no folic acid consumption before and during pregnancy, Outcome: risk of birth defects, articles collected using databases such as PubMed, Google Scholar, and Science Direct used. The articles obtained will be filtered using the stages according to the PRISM flow diagram. The analysis was carried out using RevMan 5.3.Results: A total of 9 articles, including 6 articles from the Asian continent, namely China, Japan, India, and Bangladesh, 2 articles from the Americas, namely Mexico and New York, and 1 from the African continent, namely Ethiopia. Wherefrom the meta-analysis of 9 articles, it is known that adherence to folic acid supplementation can reduce the risk of birth defects in pregnant women (aOR= 0.69; 95% CI= 0.50 to 0.96; p= 0.003).Conclusion: Adherence to folic acid supplementation can help reduce the risk of birth defects in pregnant women.Keywords: pregnant women, folic acid, birth defects.Correspondence:Fathia Mutiara Zahra. Study Program of Pharmacy, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: efemzahra31@student.uns.ac.id. Mobile: +62815-67987661.Journal of Health Promotion and Behavior (2022), 07(02): 97-107DOI: https://doi.org/10.26911/thejhpb.2021.07.02.02